2015
DOI: 10.1089/mdr.2014.0104
|View full text |Cite
|
Sign up to set email alerts
|

The Helicobacter pylori Resistance Rate to Clarithromycin in Iran

Abstract: The resistance rate to clarithromycin in Iran is high. H. pylori clarithromycin-resistant strains were not associated with sex, age, and disease. The A2143G mutation in clarithromycin-resistant H. pylori strains was the predominant finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
2
6
1
Order By: Relevance
“…The prevalence of H. pylori infection varies among different regions even in the same country (20,21). The rate of bacteria isolation in our study (31.4%) was similar to several other studies (22)(23)(24)(25). In this study, H. pylori frequency was higher in gastritis cases (63%) and there was a significant correlation with clinical outcome, but in two other studies this association was found with PUD (26,27).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of H. pylori infection varies among different regions even in the same country (20,21). The rate of bacteria isolation in our study (31.4%) was similar to several other studies (22)(23)(24)(25). In this study, H. pylori frequency was higher in gastritis cases (63%) and there was a significant correlation with clinical outcome, but in two other studies this association was found with PUD (26,27).…”
Section: Discussionsupporting
confidence: 91%
“…The global average mutation frequency for the A2143G and A2142G mutations are 69.8% and 11.7%, respectively (23). In many studies, the point mutations A2142G (13,18,23,24) and/or A2142C (4,13,21,24) were not found, and numerous investigations reported that A2143G was the only detected mutation or the most prevalent (4,5,13,17,18,(21)(22)(23)(24)(25). On the other hand, it has been found that the presence of the A2143G point mutation, but not of A2142G or A2142C, significantly lowered the H. pylori eradication rate (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…This correlation was not confirmed in a similar study by Khademi et al (24). The clarithromycin MICs for the strains isolated in Iran were in the range of 0.016 µg to 256 µg (25). These values are apparently lower than those reported in other countries.…”
Section: Discussionmentioning
confidence: 54%